2005
DOI: 10.1016/j.ab.2005.06.037
|View full text |Cite
|
Sign up to set email alerts
|

A surface plasmon resonance-based assay for small molecule inhibitors of human cyclophilin A

Abstract: A simple protocol for generating a highly stable and active surface plasmon resonance (SPR) sensor surface of recombinant human hexahistidine cyclophilin A (His-CypA) is described. The sensor surface was sensitive and stable enough to allow, for the first time, the screening and ranking of several novel small-molecule (Mr approximately 250-500 Da) ligands in a competition binding assay with cyclosporin A (CsA). It also allowed us to accurately determine the kinetic rate constants for the interaction between Hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
49
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 47 publications
6
49
0
Order By: Relevance
“…Cyp D and in consequence inhibits the formation of mPTP opening [22,37]. Therefore, since Spongionella compounds shown the same effect than CsA, Cyp D was checked as cellular target for them.…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%
“…Cyp D and in consequence inhibits the formation of mPTP opening [22,37]. Therefore, since Spongionella compounds shown the same effect than CsA, Cyp D was checked as cellular target for them.…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%
“…Use of Ni-NTA biosensors has not found widespread use for the study of His-tagged proteins in part because of the relative instability of the nickel complex (40). For example, investigators found that it was necessary to covalently couple monomeric His-tagged cyclosporine A to the biosensor, circumventing the potential advantages of the tag (41). It is likely that the unusually stable binding of trimeric NCRD proteins to the Ni-NTA biosensor results from cooperative interactions of the three hexahistidine tags of each trimer with the Ni 2Ï© -activated NTA surface.…”
Section: Molecular Modeling Provides a Potential Mechanism For The Enmentioning
confidence: 99%
“…SPR competition experiments were performed as essentially described previously (36). Met 928 was immobilized to a CM5 chip using the amine coupling method.…”
Section: Competition Assaysmentioning
confidence: 99%